BIODEGRADABLE PLASTICS FROM A MIXTURE OF LOW DENSITY POLYETHYLENE (LDPE) AND CASSAVA STARCH WITH THE ADDITION OF ACRYLIC ACID - Susilawati Susilawati; Irfan Mustafa; Desy Maulina (Jurnal Natural, 2011)
A research of preparation biodegradable plastics, from LDPE and cassava starch mixture with the addition of acrylic acid, had been conducted. This research purpose to  studied compatibility properties of the material and percent weight loss during the biodegradation test. Optimum weight loss (59,26% ) was showed after 60 days witches LDPE and starch composition ratio 6 : 4 (w/w)  while tensile strength  equal to 0,38 Kgf/mm2.  SEM characterization showed that biodegradation has occurred by  formation of hole in the biodegradable plastic surface. DTA test gave Tg = 130 °C, Tm = 230 °C and Td = 370-450 °C while FT-IR analysis showed that the biodegradable plastics have a chemistry interaction.